Efektivitas Komik Digital Berbasis Folklor Cupak Gurantang terhadap Peningkatan Literasi dan Internaliasi Nilai Karakter Siswa Sekolah Dasar - Gozin Najah Rusyada; Irfan Hidayat; Muhammad Tahir; Nurul Kemala Dewi; Windani Gheniefa (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the effectiveness of using digital comics based on the Cupak Gurantang folklore in improving reading literacy and the internalization of character values among elementary school students. The study employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group. The research subjects were 30 fifth-grade students at SDN 1 Jenggala, North Lombok Regency, who were divided into an experimental group and a control group. The research instruments included a reading literacy test, a character values questionnaire, and a student engagement observation sheet. The data were analyzed using descriptive statistics, an independent samples t-test, and N-Gain calculations. The results showed that the experimental group experienced a higher increase compared to the control group. The results of the study indicate that the experimental group showed a greater improvement than the control group. The average reading literacy score increased from 62.40 to 85.13 (N-Gain 0.72; high category), while that of the control group increased from 61.87 to 73.27 (N-Gain 0.38; moderate category). In terms of character values, the experimental group improved from 69.33 to 87.20 (N-Gain 0.70; high category), while the control group improved from 68.93 to 76.07 (N-Gain 0.35; moderate category). Statistical test results showed a significant difference (p < 0.05), and student engagement in the experimental group was in the high category. These findings confirm that the Cupak Gurantang folklore-based digital comic is effective in improving reading literacy and the internalization of character values among elementary school students